Chinese infrastructure projects in Argentina and land grabbing mechanisms: an analysis from land governance - Mora, Sol Yamila (2023)
This article analyzes the influence of land governance on land control mechanisms involved in Chinese infrastructure projects in Argentina. Based on a dialogue between the neo-Gramscian approach to International Political Economy and Political Ecology and critical agrarian studies, it is argued that land-grabbing mechanisms are conditioned by the power relations at multiple scales that configure land governance. Therefore, these modalities do not only depend on the investor but are shaped by the actions and discourses of various actors involved in land governance in the host state. The multiple mechanisms involved in two Chinese projects are organized into a typology that shows that land governance facilitated the predominance of consensual land control mechanisms, although coercion was central to supporting these modalities.